International demand for higher education: the industry, the theory and the model / Fadli Fizari Abu Hassan Asari, Suriyani Muhamad and Puteri Zarina Megat Khalid - Abu Hassan Asari, Fadli Fizari; Muhamad, Suriyani; Megat Khalid, Puteri Zarina (2017)
International demand for higher education is experiencing a remarkable growth. It is expected that a total of 8.3 million tertiary students will be scattered all around the world by 2020. This is due to an annual growth of 8%, assisted by the upsurge in supply and demand. High return from this industry attracts participation from more countries and further challenges the traditional providers. Hence, this article is a literature review on international demand for higher education which links between the industry, the theory and the model. In details, this paper provides a basic idea and current progress of the industry. In addition, the human capital theory associated with the industry is included. For the purpose of empirical analysis, appropriate model is proposed to enable more future studies.